Multidrug Resistance and Molecular Characterization of Streptococcus agalactiae Isolates From Dairy Cattle With Mastitis - Hernandez, Luciana; Bottini, Enriqueta; Cadona, Jimena; Cacciato, Claudio; Monteavaro, Cristina; Bustamante, Ana; Sanso, Andrea Mariel (Frontiers in Cellular and Infection Microbiology, 2021)
Streptococcus agalactiae is a pathogen-associated to bovine mastitis, a health disorder responsible for significant economic losses in the dairy industry. Antimicrobial therapy remains the main strategy for the control of this bacterium in dairy herds and human infections. In order to get insight on molecular characteristics of S. agalactiae strains circulating among Argentinean cattle with mastitis, we received 1500 samples from 56 dairy farms between 2016 and 2019. We recovered 56 S. agalactiae isolates and characterized them in relation to serotypes, virulence genes, and antimicrobial susceptibility. Serotypes III and II were the most prevalent ones (46% and 41% respectively), followed by Ia (7%). In relation to the 13 virulence genes screened in this study, the genes spb1, hylB, cylE and PI-2b were present in all the isolates meanwhile, bca, cpsA, and rib were detected in different frequencies, 36%, 96%, and 59%, respectively. On the other hand, bac, hvgA, lmb, PI-1, PI-2a and scpB genes could not be detected in any of the isolates. Disk diffusion method against a panel of 8 antimicrobial agents showed an important number of strains resistant simultaneously to five antibiotics. We also detected several resistance-encoding genes, tet(M), tet(O), ermB, aphA3 and lnu(B) (9%, 50%, 32%, 32% and 5%, respectively). The results here presented are the first molecular data on S. agalactiae isolates causing bovine mastitis in Argentina and provide a foundation for the development of diagnostic, prophylactic, and therapeutic methods, including the perspective of a vaccine.